The roles and therapeutic potentialof mesenchymal stem/stromal cells and their extracellular vesicles in tendinopathies - Quintero, Daniel; Perucca Orfei, Carlotta; Kaplan, Lee D.; de Girolamo, Laura; Best, Thomas M.; Kouroupis, Dimitrios (Frontiers in Bioengineering and Biotechnology, 2023)
Tendinopathies encompass a highly prevalent, multi-faceted spectrum of disorders, characterized by activity-related pain, compromised function, and propensity for an extended absence from sport and the workplace. The pathophysiology of tendinopathy continues to evolve. For decades, it has been related primarily to repetitive overload trauma but more recently, the onset of tendinopathy has been attributed to the tissue’s failed attempt to heal after subclinical inflammatory and immune challenges (failed healing model). Conventional tendinopathy management produces only short-term symptomatic relief and often results in incomplete repair or healing leading to compromised tendon function. For this reason, there has been increased effort to develop therapeutics to overcome the tissue’s failed healing response by targeting the cellular metaplasia and pro-inflammatory extra-cellular environment. On this basis, stem cell-based therapies have been proposed as an alternative therapeutic approach designed to modify the course of the various tendon pathologies. Mesenchymal stem/stromal cells (MSCs) are multipotent stem cells often referred to as ‘medicinal signaling cells’ due to their immunomodulatory and anti-inflammatory properties that can produce a pro-regenerative microenvironment in pathological tendons. However, the adoption of MSCs into clinical practice has been limited by FDA regulations and perceived risk of adverse events upon infusion in vivo. The introduction of cell-free approaches, such as the secretome and extracellular vesicles of MSCs, has encouraged new perspectives for the treatment of tendinopathies, showing promising short-term results. In this article, we review the most recent advances in MSC-based and MSC-derived therapies for tendinopathies. Preclinical and clinical studies are included with comment on future directions of this rapidly developing therapeutic modality, including the importance of understanding tissue loading and its relationship to any treatment regimen.